Management Strategies for Enhancing the Quality of Student Learning Processes in the Digital age - Nutfatin Abiadhoh; Na’imah Na’imah; Restu Agestiningrum (Eduvest - Journal of Universal Studies, 2026)
This research aims to describe management strategies for strengthening the quality of students' learning processes in the digital era at SDIT Nurul Hayah Ketanggungan Brebes. The study is motivated by the need for elementary schools to respond to digital transformation pedagogically so that technology can optimally support learning quality. A qualitative approach with a case study design was employed, with data collected through observation, in-depth interviews, and documentation involving the principal, teachers, and educational staff as informants. Data analysis was conducted through data reduction, data display, and interactive conclusion drawing. The findings reveal that management strategies for strengthening the quality of students' learning processes in the digital era have been implemented systematically, with management playing a crucial role in strengthening learning quality through strategic planning, organization, implementation, and evaluation. The implications of these strategies are reflected in increased student engagement, learning flexibility, and the development of 4C competencies (critical thinking, creativity, collaboration, and communication) as well as digital literacy. This study contributes to the development of digital-based educational management at the elementary school level, confirming that school management has a significant role in improving the quality of students' learning processes in the digital era.